Non-invasive activation of optogenetic actuators - Birkner, Elisabeth (2014)
The manipulation of genetically targeted neurons with light (optogenetics) continues to provide unprecedented avenues into studying the function of the mammalian brain. However, potential translation into the clinical arena faces a number of significant hurdles, foremost among them the need for insertion of optical fibers into the brain to deliver light to opsins expressed on neuronal membranes. In order to overcome these hardware-related problems, we have developed an alternative strategy for delivering light to opsins which does not involve fiber implants. Rather, the light is produced by a protein, luciferase, which oxidizes intravenously applied substrate, thereby emitting bioluminescence. In proof-ofprinciple studies employing a fusion protein of a light-generating luciferase to a light-sensing opsin (luminopsin), we showed that light emitted by Gaussia luciferase is indeed able to activate channelrhodopsin, allowing modulation of neuronal activity when expressed in cultured neurons. Here we assessed applicability of the concept in vivo in mice expressing luminopsins from viral vectors and from genetically engineered transgenes. The experiments demonstrate that intravenously applied substrate reaches neurons in the brain, causing the luciferase to produce bioluminescence which can be imaged in vivo, and that activation of channelrhodopsin by bioluminescence is sufficient to affect behavior. Further developments of such technology based on combining optogenetics with bioluminescence - i.e. combining lightsensing molecules with biologically produced light through luciferases - should bring optogenetics closer to clinical applications.